Meat flavour in pork and beef – From animal to meal. (October 2017) - Aaslyng, Margit D.; Meinert, Lene
Abstract: An intense meat flavour is greatly appreciated by consumers. Meat flavour is generated during the cooking process through a complex series of chemical reactions between precursors, intermediate reaction products and degradation products. The content and nature of the precursors present in the meat are affected by several factors including genetics, feed, handling of the live animals and subsequent handling of the meat. The fatty acid composition can easily be altered though feeding, especially in monogastric animals, while the carbohydrate content is more closely related to genetics (pigs), feeding in the last days before slaughter and handling at slaughter (both ante and post mortem). Ageing of the meat is not particularly important for the flavour, unless the meat is dry-aged. In comparison, cooking is crucial for the development of flavour. Highlights: Meat flavour generated during heating depends on the content of the precursors. The content of precursors is related to genetics, feed and handling at slaughter. Fatty acid composition can be altered through feeding. Carbohydrate composition is particularly related to handling at slaughter. Cooking is essential in meat flavour development.